Telaah Ayat Al-Quran Surah Al-Kautsar - Ani Marlia; Devita Syaharani; Nopi Sari; Imelda; Nola Riski Amelia; Ali Machmud Badarudin; Arief Armando; Anita Kurnia Sari (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
The first verse in Surah Al Kautsar contains the many gifts from Allah Subhanahu Wa Ta'ala to the Prophet Muhammad Shallallahu Alaihi Wasallam and his people. God has given so many great blessings that humans cannot count them.The second verse explains Allah Subhanahu Wa Ta'ala, who commands humans to pray and perform sacrifices. In Ibn Jarir's history, the second verse of Al Kautsar's letter came down during the Hudaibiyah War. At that time, the angel Gabriel came down to earth to give the wakyu of Surah Al Kautsar verse 2 at the command of Allah.In Surah Al Kautsar verse 3, people who hate the Prophet Muhammad are called abtar people. They are a group of people who are cut off from the goodness and grace of Allah Subhanahu Wa Ta'ala.